PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL di D.I YOGYAKARTA TAHUN 2012-2016 - Riska Rahmawati; Achmad Tjahjono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
This study aims to determine the effect of Regional Taxes, Regional Retribution, General Allocation Funds, Special Allocation Funds on the allocation of Capital Expenditures in DI Yogyakarta Region consisting of five Regencies / Cities for the period of 2012-2016. This study is analyzing the variable X against variable Y. Design The study was compiled based on APBD data in the Realization of DI Yogyakarta Regional Revenues and Expenditures in 2012-2016 taken from BPS DI Yogyakarta with a sample data on Regional Taxes, Regional Retribution, General Allocation Funds, Special Allocation Funds, and Capital Expenditures. The variables used are Local Tax (X1), Regional Retribution (X2), General Allocation Fund (X3), Special Allocation Fund (X4), and Capital Expenditure (Y). The analysis for testing in this study used SPSS.20, the techniques used were Multiple Regression Analysis, T Test, F Test, and Determination Coefficient Test. The results of this study indicate that partially Regional Levies and Special Allocation Funds do not have a significant effect on Capital Expenditures, while Regional Taxes and Special Allocation Funds have an influence on Capital Expenditures, simultaneously Regional Taxes, Regional Retribution, General Allocation Funds, and Allocation Funds Specifically has a significant influence on Capital Expenditures. The magnitude of the influence of Regional Taxes, Regional Retibusi, General Allocation Funds, and Special Allocation Funds on Capital Expenditures is 77.8 percent while the remaining 22.2 percent is explained by other factors.